Unions, Tripartite Competition and Innovation - Alex Bryson; Harald Dale-Olsen (Institute of Labor Economics (IZA), 2020)
We present theoretical and empirical evidence challenging results from early studies that found unions were detrimental to workplace innovation. Under our theoretical model, which extends the Cournot duopoly innovation model, local union wage bargaining is more conducive to innovation - particularly product innovation - than competitive pay setting. We test the theory with workplace data for Britain and Norway. Results are consistent with the theory: local union bargaining is positively associated with product innovations in both countries. In Norway, local union bargaining is also positively associated with process innovation.
Keywords: J28; J51; J81; L23; O31; 330; product innovation; process innovation; trade unions; collective bargaining